A WORLD OF OPPOSITES - Malin, Gray (New York, NY : Abrams Appleseed, 2020)
Join Gray Malin as he explores the concept of opposites through his eye-popping photographs taken from Antarctica to Africa. Readers will delight in journeying from the barren desert landscape of Namibia (Dry) to the crashing teal waves of the Australian ocean (Wet). His bright and colourful photographs hold heaps of kid appeal, satisfying young readers' sense of imagination and innate desire to learn more about the world.
Preschool.
Keywords: English language -- Synonyms and antonyms -- Juvenile literature; Vocabulary -- Juvenile literature; Photography, Artistic -- Juvenile literature; Picture books for children; Creative nonfiction